Effect of fluoride in drinking water on children's intelligence in high and low fluoride areas of Delhi - Hansa Kundu; P Basavaraj; Ashish Singla; Ritu Gupta; Khushboo Singh; Swati Jain (Wolters Kluwer Medknow Publications, 2015)
Introduction: Fluoride is one of the indispensable elements for the living being. However, the intake of F above the threshold level can affect the central nervous system even before causing dental or skeletal fluorosis. Aim: The aim was to assess the effect of fluoride in drinking water on the intelligence quotient (IQ) of 8-12 years old school going children residing in high and low Fluoride (F) areas of Delhi. Materials and Methods: A total of 200 school children were selected, 100 from low F area and 100 from high F area. The IQ of the children was assessed using Ravens Standardized Progressive Matrices Test. Information for each child's sociodemographic data, mother's diet during pregnancy, duration of residency in the village, source of drinking water, and duration of drinking water from the source was entered on a specially designed proforma from mothers of children. Height and weight were also recorded for each child to assess the nutritional status. Independent t-test and Chi-square test was used to compare mean IQ scores in high and low fluoridated areas. Pearson's correlation and multivariate linear regression were used to appraise the issue of all the study variables on IQ. Results: Comparison of mean IQ of children in both high (76.20 ± 19.10) and low F (85.80 ± 18.85) areas showed a significant difference (P = 0.013). Multiple regression analysis between child IQ and all other independent variables revealed that mother's diet during pregnancy (P = 0.001) along with F in drinking water (P = 0.017) were the independent variables with the greatest explanatory power for child IQ variance (r2 = 0.417) without interaction with other variables. Conclusion: Fluoride in the drinking water was significantly related with the IQ of children. Along with fluoride, mother's diet during pregnancy was also found to be significantly related with IQ of children. Researches in the same field are further advocated with large sample size and over a large geographical area.